La scultura blu - Fagioli, Massimo (Il sogno della farfalla, 2006)
One month after the debate held on 23 October 2005 and published consequently in this magazine, Fagioli continues to deepen his research into art, language and the relationship between men and women on the occasion of the presentation of his sculpture located in the courtyard of the Faculty of Oriental Studies at the University of “La Sapienza”, Rome. Starting from some considerations on the significance of the sculpture and going over the phases of his long research into images and into nonconscious thought, Fagioli sees in the birth of writing the possible moment of origin of a Western identity based on reason and consequently on the scission between reason and irrationality thus condemning women to a condition of inferiority.